Characteristic of Vicarious Liability - Avtandil Natsvaladze (European Scientific Journal, ESJ, 2017)
Vicarious liability may be determined as the liability of one party for the damage caused by a third party. Unlike personal liability, a person is responsible for the damage who is not guilty and is not involved in the occurrence of the harm. It is believed that it is unfair to impose the liability to a person for a harmful action of others; however, it is considered that this rule serves to the principles of fairness. 21 The legal principle of vicarious liability is accepted in society. This is the occurrence when unification of the risk and interest takes place. A person who engages another person for fulfilling his/her goals easily determines the result. Accordingly, the probability of the occurrence of damage by the agent objectively increases.22 In this regard, it is paramount to define the preconditions according to which, responsible persons are determined for indemnification. This issue is differently regulated under Georgian and foreign legislations.